2023
DOI: 10.1038/s41598-023-37587-y
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing acute malnutrition by educational inequality of mother’s among under five children in Jammu and Kashmir

Abstract: Health outcomes in the state of Jammu and Kashmir have shown improvement in recent decades. However, nutritional achievements, particularly among children under the age of five, have not seen similar progress. Various factors influence the nutritional status of this age group, with the socio-cultural and biological attributes of mothers being considered significant determinants. While some studies have examined these attributes, there is a scarcity of research exploring the causal link between socio-culturally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In Indian settings, mothers are the primary caregivers of children, and therefore, a significant linkage between mother’s education and child health has been observed in many previous studies 33 . For instance, the risk of malnutrition and mortality among under-five children is more common among children with lower-educated mothers than their higher-educated counterparts 34 36 .The current study found that mother’s age is an another individual-level factor of child stool disposal practices among the study participants, particularly in rural settings. In addition, the unsafe disposal practice of child stool is prevalent among teenage mothers in rural areas.…”
Section: Discussionmentioning
confidence: 53%
“…In Indian settings, mothers are the primary caregivers of children, and therefore, a significant linkage between mother’s education and child health has been observed in many previous studies 33 . For instance, the risk of malnutrition and mortality among under-five children is more common among children with lower-educated mothers than their higher-educated counterparts 34 36 .The current study found that mother’s age is an another individual-level factor of child stool disposal practices among the study participants, particularly in rural settings. In addition, the unsafe disposal practice of child stool is prevalent among teenage mothers in rural areas.…”
Section: Discussionmentioning
confidence: 53%
“…As the education level of mothers increased, the chances of their children being at risk of having SAM decreased. The past literature has also highlighted the importance of a mother's education for the occurrence of SAM [32][33][34][35] . Mothers' education appears to be so impactful for children's nutrition as an educated mother is better equipped with knowledge and awareness regarding child care.…”
Section: Discussionmentioning
confidence: 99%
“…In order to raise the educational attainment of Kashmiri women, a number of issues, such as sociocultural norms, economic circumstances, and security concerns, must be addressed. Tariq et al (2023) identified the relationship between mothers' educational attainment and stunting in children under five in J&K and concluded that children whose mothers are literate had a reduced risk of stunting than children whose mothers are illiterate. It is still crucial to acknowledge the role of education in empowering women and promoting societal development.…”
Section: Literature Reviewmentioning
confidence: 99%